The role of LRRK2 in Parkinson’s disease : from function to dysfunction - Guerreiro, Patricia I. da Silva (2015)
Tese de doutoramento, Ciências Biomédicas (Neurociências), Universidade de Lisboa, Faculdade de Medicina, 2015